Ageing, maturation and seasonal growth of the Argentine short-finned squid lIlex argentinus (Cephalopoda: Ommastrephidae) commercially fished in southern Brazil - Bainy, Mara Cristiane Rodrigues Silveira (2011)
Dissertação(mestrado) - Universidade Federal do Rio Grande, Programa de Pós–Graduação em Oceanografia Biológica, Instituto de Oceanografia, 2011.